Public debt, economic growth, and inflation in African economies - Veiga, J. L.; Ferreira-Lopes, A.; Sequeira, T. N. (South African Journal of Economics, 2016)
We analyse the relationship between public debt, economic growth and inflation in a group of 52 African economies between 1950 and 2012. The results indicate that the limits of public debt are negatively related to economic growth and exhibit, from a given level of debt, an inverted U behaviour regarding the relationship between economic growth and public debt. Briefly, the high levels of public debt are coincident with reduced rates of economic growth and rising levels of inflation. Our results for three specific geographical areas resemble those of the overall analysis, despite some differences. In North African countries, the growth rates of the GDP and inflation also show an inverted U behaviour as the ratio of public debt/GDP increases. The highest rate of economic growth is recorded when the ratio public debt/GDP is below 30% of GDP and corresponds to an average inflation rate of 5.33%. Identical behaviour of the GDP growth rates and inflation also appears in Sub-Saharan countries until the third interval (60-90%). However, the highest growth rate of the GDP and GDP per capita is registered when the public debt/GDP ratio is in the second interval (30-60%). For SADC countries, the highest average rate of economic growth (6.8%) is similar to North African countries, when the ratio public debt/GDP is below 30% of GDP, with an average inflation rate of 11%. A number of robustness analyses were performed and the great majority of them confirm the general analysis.